Psychological Factors Associated with Voluntary Work and its Commitment - González, Luis; Leiva, Yirlén; Sepúlveda, Andrés; Vega, Carolyne (Revista de Psicología, 2004)
The present investigation explores the motivations associated to the permanency of the volunteers in the Institution of Home of Christ. Starting from the adaptation of two instruments based on the functional theory of the motivation of Omoto and Snyder, the VFI and the VSS, they think about three hypothesis to explore the characteristics of these motivations and the list that it plays the organization as long as satisfaction of the entrance reasons. It is found that the volunteers that remain in the institution obtain higher punctuations that the voluntary deserters in the total motivation, motivations guided to values and motivations guided to self–esteem. Likewise it was found that the volunteers that remain in the institution present motivations guided to more marked values, even when he/she was not significant correlation between time of permanency and motivations heterocentradas. Lastly, it was not found that the grade of satisfaction in the organization for the entrance motivations had a decisive list in the time of permanency.